Scarcity and instability: Transforming societies through equitable distribution mechanisms - Patel, Jaynisha; Lucey, Amanda (Journal of Regional Security, 2024)
Under the framework of SDG 16, one key underexplored area of inclusion relates to the means of ensuring access to justice through the equitable governance of scarce resources, and mechanisms to promote equal and structural access to opportunities across society. This research sets out to answer the following questions across three case studies: (1) What is the relationship between critical or scarce resources and political conflict in the region under study?; (2) On what basis is the scarce or critical resource currently distributed within the region under study?; (3) What formal or informal governance mechanisms are in place to manage access to critical or scarce resources, and resolve conflicts created by it?; and (4) What improvements could be made to ensure more inclusive and equitable access to the distribution of this resource? The three proposed case studies, namely, Central Mali (land), Northeastern Kenya (water), and northern Mozambique (extraction and revenues of natural gas), have unique political and geographic features that are indivisible from peace and security. In each case, a blend of formal and informal mechanisms is used, but these often involve competing mandates, are guided by socio-economic dynamics or are unenforced, potentially leading to different types of localised conflict.